A Coptic letter written to a former draconarius by Serenus, son of Donatus (P.Heid. Inv. Kopt. 241) - Vanderheyden, Loreleï (Journal of Coptic studies, 2023)
The papyrus P.Heid. Kopt. 241 is exceptional in many respects: it is in an almost perfect state of preservation, the correspondents involved probably belong to a military milieu, and its non-standard Coptic makes it valuable for the study of the Middle Egyptian dialect. This letter shows that the official languages of the Empire, namely Greek or Latin, were not the only languages used for written communication with veterans or former officials, and emphasizes that Coptic sources should also be taken into consideration when working on Late Antique administration.
Gesehen am 09.08.2024